2016
DOI: 10.1177/0956797616667459
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Types of Perspective Taking

Abstract: Sex differences in favor of males have been documented in measures of spatial perspective taking. In this research, we examined whether social factors (i.e., stereotype threat and the inclusion of human figures in tasks) account for these differences. In Experiment 1, we evaluated performance when perspective-taking tests were framed as measuring either spatial or social (empathetic) perspective-taking abilities. In the spatial condition, tasks were framed as measures of spatial ability on which males have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(46 citation statements)
references
References 32 publications
3
37
1
Order By: Relevance
“…Stereotype threat not only affects test performance but can also evoke more negative attitudes toward stereotyped domains (Good et al 2012). This phenomenon has been increasingly investigated in a wide range of domains such as mathematics (e.g., Aronson et al 1999), intelligence (e.g., McKay et al 2002), spatial orientation (e.g., Tarampi et al 2016) and memory (e.g., Chasteen et al 2005). The effect has been shown to occur especially when the tasks were difficult (Spencer et al 1999) or required new solving strategies (Carr and Steele 2009).…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%
“…Stereotype threat not only affects test performance but can also evoke more negative attitudes toward stereotyped domains (Good et al 2012). This phenomenon has been increasingly investigated in a wide range of domains such as mathematics (e.g., Aronson et al 1999), intelligence (e.g., McKay et al 2002), spatial orientation (e.g., Tarampi et al 2016) and memory (e.g., Chasteen et al 2005). The effect has been shown to occur especially when the tasks were difficult (Spencer et al 1999) or required new solving strategies (Carr and Steele 2009).…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%
“…No gender differences were found in PTSOT or STAT gains. Some work has suggested that there is a sex difference in PTSOT performance [49], while others did not find differences [50]. We have not found previous information on gender data with the STAT.…”
Section: Discussionmentioning
confidence: 60%
“…Given that VSP taking did not occur in a spatial memory-based task (Kelly et al, 2018), it is important that the affordance of co-users is always displayed in a smart home controller for effective interface design. In addition, the human figure affordance (Tarampi et al, 2016) is suitable for mental simulation to deal with information such as SA Level 1.…”
Section: Discussionmentioning
confidence: 99%